2017
DOI: 10.1055/s-0043-101918
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Promoting Physical Activity and Balanced Diets in a Primary School Setting with a High Proportion of Migrant School Children

Abstract: Children with migration background are at particular risk for overweight. We assessed the effects of a primary school-based initiative targeted at enhancing physical activity and dietary education among children with a high proportion of migration background. Four 3 and 4 grade classes (n=70 children, 77% with migration background) participated in a 10-months intervention comprising 2 additional exercise lessons weekly and 10 nutrition lessons per school year. 6 school classes (n=125 children, 65% with migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…1, ▶table 1). The target group of the SMS initiative comprises children with an increased need for support for a balanced lifestyle and the prevention of lifestyle-related diseases [6]. This is reflected by the high proportion of children with migrant background in the present study cohort (▶table 1).…”
Section: Study Populationmentioning
confidence: 96%
See 2 more Smart Citations
“…1, ▶table 1). The target group of the SMS initiative comprises children with an increased need for support for a balanced lifestyle and the prevention of lifestyle-related diseases [6]. This is reflected by the high proportion of children with migrant background in the present study cohort (▶table 1).…”
Section: Study Populationmentioning
confidence: 96%
“…Limitations comprise, firstly, that the children could not be matched for migration background and age due to the school-based setting. However, these variables were included as confounders in the mixed models and regression analyses to minimize possible effects on the results [6]. Second, the participating school classes could not be randomly allocated to the intervention and control group as the practical nutrition lessons are part of the SMS initiative.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous fundamental movement skill intervention studies have shown promising outcomes on MVPA levels in children [ 19 , 20 , 21 , 22 , 23 ]. In contrast, some studies have demonstrated that fundamental movement skill interventions are unsuccessful at improving physical activity levels in children [ 24 , 25 , 26 , 27 ]. Robinson and Goodway [ 28 ] infer that children do not drastically improve their fundamental movement skill competence through free play; improvements are only seen when in an instructed environment and when progressions are apparent.…”
Section: Introductionmentioning
confidence: 99%
“…Regular monitoring of body weight is also crucial and, to that end, regular check-ups are advised [4]. Additional exercise classes and nutrition-centred educational lessons are further recommended [32].…”
Section: Discussionmentioning
confidence: 99%